"It's all interconnected… like a spider web": a qualitative study of the meanings of food and healthy eating in an Indigenous community. Issue 1 (1st January 2019) - Goettke, Emma; Reynolds, J.
ABSTRACT: Canadian Indigenous populations are disproportionately affected by rising rates of diet-related chronic disease and have been experiencing rapid lifestyle changes affecting diet. In recognition of these issues, this study aimed to obtain greater understanding of attitudes and meanings around healthy eating in a semi-remote community in Eeyou Istchee. A qualitative study design used semi-structured interviews and observational field notes to explore local accounts of food and health. Two distinct versions of "healthy eating" were identified: one relating to traditional food and preparation methods; the other reflecting medicalised accounts of illness and diagnosed conditions. The latter links with "southern" modes of accessing and preparing food, demonstrating local capacity to adapt to the rapid changes in body, lifestyle and environment being experienced. New connections, associating non-native ways with traditional practices, are being formed where traditional ways of living on the land have been severed. These local accounts show how people are continually negotiating different constructs of "healthy eating." These findings expand current understandings of the context of food and healthy eating in Eeyou Istchee, emphasising present-day and historical experiences of the land. Future research and diet-related health interventions must continue to acknowledge and incorporate local understandings of health to help address the broader socio-political factors that shape Indigenous lifestyles, environments and health.